Distribution of Hypertension Cases Based on Primary Health Care 2017–2021 in Malang, Indonesia: Spatial Analysis - Imtinani, Alifia Irbah; Qurniyawati, Eny (Faculty of Medicine Universitas Padjadjaran, 2024)
Background: Malang Regency is one of the cities in East Java, Indonesia that has a high trend of hypertension cases. The study aimed to describe the distribution of hypertension cases at the primary health care level in Malang Regency, Indonesia using spatial analysis.Methods: This was a descriptive analysis study using secondary data obtained from the Health Profile of Malang Regency from 2017 to 2021. The total sampling method was used. Data on hypertension cases from 16 primary health cares was collected. Quantum geographic information system (QGIS) was used to visualize the distribution of cases. Data was presented in the tables and a map with different coloring based on the high-low categories of hypertension cases in a region.Results: There was a tendency for an increase in hypertension cases every year in 3 of 16 primary health care. Primary Health Cares with an increased prevalence of cases during 2017–2021 were Arjowinangun (7.65% to 24.24%), Mojolangu (17.20% to 31.57%), and Kendalsari (8.84% to 27.29%). However, cases decreased from 2017 to 2018, and experienced a very high increase from 2018 to 2019.Conclusion: The distribution of hypertension cases in Malang Regency from 2017 to 2021 tends to fluctuate from year to year. An education program for the community about a healthy lifestyle and the importance of conducting regular health checks is needed to decrease hypertension cases.